2013
DOI: 10.1007/s10461-013-0652-4
|View full text |Cite
|
Sign up to set email alerts
|

“Set it and Forget it”: Women’s Perceptions and Opinions of Long-Acting Topical Vaginal Gels

Abstract: Women’s initial understandings and anticipated acceptability of long-acting vaginal gels as potential anti-HIV microbicides was investigated by exploring the perceptibility variables associated with prototype formulations. Four focus groups with 29 women, aged 18–45, were conducted to consider gel prototypes with varied physicochemical and rheological properties. Participants responded favorably to the concept of long-acting vaginal gels as microbicides. Distinctions in understandings and stated needs regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Women appreciated the monthly regimen and the ring's discretion – no one else knew it was being used. Overall participants endorsed the viewpoint that one could ‘set and forget’ [19] the ring (Table 2, B, D). …”
Section: Resultsmentioning
confidence: 93%
“…Women appreciated the monthly regimen and the ring's discretion – no one else knew it was being used. Overall participants endorsed the viewpoint that one could ‘set and forget’ [19] the ring (Table 2, B, D). …”
Section: Resultsmentioning
confidence: 93%
“…The attribute that participants liked most about the ring was being able to forget about it. Being worry free and able to “forget it” were salient characteristics of other topical dosage forms as well (21). The least liked attributes were related to the size and thickness of the ring, which resulted in minor insertion problems for some participants.…”
Section: Discussionmentioning
confidence: 99%
“…Women in a recent study in the United States also shared the perception that any foreign substance, such as a vaginal gel, would be invasive (van den Berg et al, 2014). One contradiction emerging from our findings relates to women’s reported reluctance to insert study gels into their vaginas, however at the same time a high reported prevalence of vaginal practices involving the insertion of ‘culturally approved’ products into the vagina.…”
Section: Discussionmentioning
confidence: 99%